Effects of cancer and non-cancer surgeries on preoperative anxiety scores of patients - (:unkn) unknown (Anestezi Dergisi, 2016)
Objective: About two-thirds of patients awaiting surgery show anxiety. Anxiety may be developed against surgery, anesthesia or the environment where they feel like a stranger. Concerns about the success of upcoming surgery, fears regarding anesthesia and postoperative pain are among the factors that determine level of preoperative anxiety. We hypothesized that patients undergoing cancer surgery may have higher preoperative anxiety scores. Method: One hundred American Society of Anesthesiologists (ASA) 1-2 patients over 18 years and scheduled to have an elective surgery were recruited. Patients undergoing a cancer surgery were in Group 1 (n=50) and undergoing a non-cancer surgery were in Group 2 (n=50). One day before the surgery, all patients were analyzed using the Amsterdam Preoperative Anxiety and Information Scale (APAIS) and the Spielberger State Trait Anxiety Inventory Test (STAI) to identify their anxiety scores. Results: Both APAIS and STAI scores of cancer patients were significantly higher compared to non-cancerous patients (p<0.001). In patients with malignancy, there was a significant negative correlation between APAIS scores and the number of previous surgeries (p<0.001). In patients undergoing non-cancer surgery, the APAIS scores of female patients were significantly higher (p=0.011). There was not a statistically significant correlation between both the APAIS and STAI scores and age, sex, education level, and marital status in patients undergoing cancer surgery. Conclusion: Both APAIS and STAI scores were found to be higher in patients having cancer surgery. We are of the opinion that, anxiolytics may be useful as premedication in the preoperative period for this patient group.
Keywords: Anxiety; APAIS; Cancer surgery; STAI